2021
DOI: 10.1186/s13018-021-02828-1
|View full text |Cite
|
Sign up to set email alerts
|

Ten-year survival of ceramic-on-ceramic total hip arthroplasty in patients younger than 60 years: a systematic review and meta-analysis

Abstract: Background Total hip arthroplasty (THA) with ceramic-on-ceramic (CoC) was created to minimise wear debris and aseptic loosening. A decade ago, a meta-analysis showed a 10-year survival rate of just 89%. Based on the excellent tribology of the current CoC, significant improvement of implant survivorship is expected. In patients younger than 60, we conducted a meta-analysis to assess 10-year survival and complications after using current primary CoC THA. Materials a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Metals are used in THA both for the fixed components (femoral stem and acetabular component) as well as for the mobile components (femoral head and liner). It should be mentioned that MoM THA is no longer utilized [ 45 , 46 , 95 ], because metal wear debris may increase metal ion levels in serum and can generate hypersensitivity responses in the soft tissues, with harmful systemic consequences [ 96 ] such as pseudotumor formation and aseptic lymphocyte-dominated vasculitis-associated lesions (ALVAL), leading to eventual soft tissue and bone destruction [ 97 ]; due to this, MoM implants have been replaced more and more with metal-with-polymer (MoP) THA implants [ 11 ].…”
Section: Bearing Surfaces and Biomaterials Used In Primary Total Hip ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Metals are used in THA both for the fixed components (femoral stem and acetabular component) as well as for the mobile components (femoral head and liner). It should be mentioned that MoM THA is no longer utilized [ 45 , 46 , 95 ], because metal wear debris may increase metal ion levels in serum and can generate hypersensitivity responses in the soft tissues, with harmful systemic consequences [ 96 ] such as pseudotumor formation and aseptic lymphocyte-dominated vasculitis-associated lesions (ALVAL), leading to eventual soft tissue and bone destruction [ 97 ]; due to this, MoM implants have been replaced more and more with metal-with-polymer (MoP) THA implants [ 11 ].…”
Section: Bearing Surfaces and Biomaterials Used In Primary Total Hip ...mentioning
confidence: 99%
“…Ceramic materials can be used for making mobile components, the prosthetic head, and the acetabular liner, thus resulting in two ceramic-on-ceramic or ceramic-on-polyethylene friction couples, each with its advantages and disadvantages. Component fracture risk was a worry in CoC arthroplasties; however, with the newer generations of implants, when the complication rates were reduced, the use of CoC has not considerably decreased [ 45 , 95 ] and remains one of the most effective ways to prevent liner wear with wear rates of less than 0.001 mm/year compared to 0.072 mm/year in ceramic-on-UHMWPE (CoUHMWPE), 0.30 mm/year in ceramic-on-HXLPE (CoHXLPE), and 0.042 mm/year in metal-on-HXLPE (MoHXLPE) [ 129 ]. Furthermore, a very recent study from 2023 found the Delta ceramic bearing to be a viable alternative for primary and revision THA, with favourable mid-term outcomes, satisfactory survival, and a low complication rate [ 130 ].…”
Section: Bearing Surfaces and Biomaterials Used In Primary Total Hip ...mentioning
confidence: 99%
“…Although its origin is still debated, this phenomenon, occurring in CoC (in 1–21% of the cases) or MoM THA, might be favored by implant mispositioning (i.e., a too verticalized acetabular component, excessive or insufficient acetabular cup anteversion) [ 113 ]. A component fracture must be ruled out.…”
Section: Complicationsmentioning
confidence: 99%
“…Still concerning CoC prosthesis, femoral head fracture is secondary to trauma or hyperactivity [ 85 ] and leads to functional impairment, whereas acetabular fractures are rare, non-secondary to trauma, and might become symptomatic only in case of displacement [ 13 , 113 , 121 ]. Acetabular fractures may be favored by excessive anteversion and poor implantation of the insert in the metal back [ 85 ].…”
Section: Complicationsmentioning
confidence: 99%
“…Surface damage or abrasion particles can cause punctual loads and the ceramic to break [6]. Despite this disadvantage, ceramic hip implant components offer clear advantages, such as low wear compared to metal-on-polyethylene joint pairings and longer life span in situ [7,8]. Using metal adapter sleeves creates new optimal conditions for connecting the ceramic head and hip stem.…”
Section: Introductionmentioning
confidence: 99%